The impact of powerful jets on the far-infrared emission of an extreme radio quasar at z~6 - Rojas-Ruiz, Sofía; Bañados Torres, Eduardo; Neeleman, Marcel; Connor, Thomas; Eilers, Anna-Christina; Venemans, Bram P.; Khusanova, Yana; Carilli, Chris L.; Mazzucchelli, Chiara; Decarli, Roberto; Momjian, Emmanuel; Novak, Mladen (The astrophysical journal, 2021)
The interactions between radio jets and the interstellar medium play a defining role for the coevolution of central supermassive black holes and their host galaxies, but observational constraints on these feedback processes are still very limited at redshifts z > 2. We investigate the radio-loud quasar PSO J352.4034-15.3373 at z ∼ 6 at the edge of the Epoch of Reionization. This quasar is among the most powerful radio emitters and the first one with direct evidence of extended radio jets (∼1.6 kpc) at these high redshifts. We analyze NOrthern Extended Millimeter Array and Atacama Large Millimeter/submillimeter Array millimeter data targeting the CO (6-5) and [C ii] far-infrared (FIR) emission lines, respectively, and the underlying continuum. The broad 440 ± 80 km s−1 and marginally resolved [C ii] emission line yields a systemic redshift of z = 5.832 ± 0.001. Additionally, we report a strong 215 MHz radio continuum detection, 88 ± 7 mJy, using the Giant Metrewave Radio Telescope. This measurement significantly improves the constraints at the low-frequency end of the spectral energy distribution of this quasar. In contrast to what is typically observed in high-redshift radio-quiet quasars, we show that cold dust emission alone cannot reproduce the millimeter continuum measurements. This is evidence that the strong synchrotron emission from the quasar contributes substantially to the emission even at millimeter (FIR in the rest-frame) wavelengths. This quasar is an ideal system to probe the effects of radio jets during the formation of a massive galaxy within the first gigayear of the universe.
Gesehen am 29.01.2022